Entrepreneurship development in the Balkans : perspective from diverse contexts - Ramadani, Veland; Kjosev, Sasho; Sergi, Bruno S. (Lab for entrepreneurship and development., 2023)
Entrepreneurship Development in the Balkans directly engages questions of innovation and risk management within various types of entrepreneurship, including female, social, migrant, and corporate entrepreneurship in the context of the Balkans: Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Greece, Kosovo, Montenegro, North Macedonia, Romania, Serbia, Slovenia and Türkiye. This collection of in-depth studies represents a comprehensive state-of-the-art picture of entrepreneurship and small business management issues. It provides primary theoretical and empirical evidence that offers a brighter view of these fields from the perspective of the Balkans and includes contributions of highly reputed authors and experts from the region and beyond. Entrepreneurship Development in the Balkans appeals to regional and international researchers interested in learning more about entrepreneurship and small business management in the Balkans. Lab for Entrepreneurship and Development is Emerald's innovative book series on the study of entrepreneurship and development, striving to set the agenda for advancing research on entrepreneurship in the context of finance, economic development, innovation, and the society at large.